Why SPAC investors should listen to the market. - Jenkinson, T; Sousa, M (Oxford Finance, 2009)
Special purpose acquisition companies (SPACs) have raised around $22bn from investors since 2003, and comprised 20% of total funds raised in US IPOs in 2007. SPACs are interesting structures – allowing investors a risk-free option to invest in a future acquisition. However, we show that more than one-half of approved deals immediately destroy value. Investors, who can observe the market’s view of the proposed deal, as well as that of the founders, should listen to the market, since the extreme incentives faced by the SPAC founders create corresponding conflicts of interest. We propose a simple, observable rule – based on market prices – which investors should heed.